P10 Interactions of fibroblasts derived from irradiated subcutaneous connective tissue with HNSCC. Issue 5 (May 2015) - Gehrke, T.; Hackenberg, S.; Scherzad, A.; Kleinsasser, N.
Abstract : Introduction: Cancer cells show a variety of interactions with cells of the surrounding connective tissue, mainly consisting of fibroblasts. Human skin-fibroblasts which are co-cultivated with tumor cells have the ability to convert into carcinoma-associated fibroblasts (CAF's) which are known to support tumor growth and invasiveness. The aim of the current study was to determine the impact of irradiation on fibroblast-tumor interaction. Material: Primary human fibroblasts of subcutaneous connective tissue of pre-irradiated or non-irradiated skin were co-cultivated with the HNSCC cell line FaDu for 3 days. MTT assay, annexin V-propidium iodide test and ELISA were performed to analyze tumor viability, apoptosis and secretion of interleukin (IL)-6 and IL-8. Markers for epithelial-mesenchymal transition (EMT) were assessed by western blot. Results: Co-culture with pre-irradiated fibroblasts showed a significant decrease in tumor viability and an increase in apoptosis. Levels of IL-8 significantly decreased in irradiated compared to non-irradiated fibroblasts. After irradiation, the cells did not promote EMT anymore. Conclusion: Previous radiation influences fundamental properties of the complex tumor and stroma orchestration. These interactions have to be evaluated in detail in order to further illuminate possible options of intervention.